PENGARUH RETURN ON ASSET, RETURN ON EQUITY, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN NON-BANK DALAM INDEKS LQ45 TAHUN 2014-2018 - Wira Diyah Ayu Kurniati; Meylani Tuti (Panorama Nusantara, 2019)
This research aimed to determine the impact of financial ratios to stock price. The object of this research is Nonbank Companies on Index LQ45 2014 to 2018. The financial ratios used in this study as independent variables were Return On Asset (ROA), Return On Equity (ROE) dan Earning Per Share (EPS). The data used in this research were annual report, based on annual financial reports, starting from the first year of 2014 to 2018. The data used in this study is the use of panel data methods and Purposive Sampling is done by comparing the regression model (1) Ordinary Least Square (common effect), (2) Efek Tetap (Fixed Effects), (3) Efek Random (Random Effect). Of the three models obtained the best model is Fixed Effect.The results of this study indicate that ROA and ROE have the relationship to the stock price, but not significant. While, the EPS has showed a significant effect on stock price. However ROA, ROE have significantly affected stock prices, simultaneously.